Biological Activities and Composition of Ferulago carduchorum Essential Oil - Fereshteh Golfakhrabadi; Mahnaz Khanavi; SeyedNasser Ostad; Soodabeh Saeidnia; Hassan Vatandoost; MohammadReza Abai; Mitra Hafizi; Fatemeh Yousefbeyk; Yaghoob RazzaghiRad; Ameneh Baghenegadian; MohammadReza Shams-Ardekani (Tehran University of Medical Sciences, 2015)
Background: Ferulago carduchorum Boiss and Hausskn belongs to the Apiaceae family. This plant grows in west part of Iran that local people added it to dairy and oil ghee to delay expiration date and give them a pleasant taste. The aim of this study was to investigate the antioxidant, antimicrobial, acetyl cholinesterase inhibition, cytotoxic, larvicidal activities and composition of essential oil of F. carduchorum. Methods: Acetyl cholinesterase (AChE) inhibitory, larvicidal activities and chemical composition of essential oil of F. carduchorum were investigated. Besides, antioxidant, antimicrobial and cytotoxic activities of essential oil were tested using DPPH, microdilution method and MTT assay, respectively. Results: The major components of essential oil were (z)-β-ocimene (43.3%), α-pinene (18.23%) and bornyl acetate (3.98%). Among 43 identified components, monoterpenes were the most compounds (84.63%). The essential oil had noticeable efficiency against Candida albicans (MIC= 2340 μg ml-1) and it was effective against Anopheles stephensi with LC50 and LC90 values of 12.78 and 47.43 ppm, respectively. The essential oil could inhibit AChE (IC50= 23.6 μl ml-1). The essential oil showed high cytotoxicity on T47D, HEP-G2 and HT-29 cell lines (IC50< 2 μg ml-1). Conclusion: The essential oil of F. carduchorum collected from west of Iran had anti-Candida, larvicidal and cytotoxicity effects and should be further investigated in others in vitro and in vivo experimental models.